Global Trends on Electronic Learning and Entrepreneurship: Bibliometric Analysis (2001 – 2022) - Indira, Fransisca Rahcmawati; Wardani, Dewi Kusuma; Murwaningsih, Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The use of electronic learning in entrepreneurship education will increase entrepreneurial intentions and behaviors in university students. The purpose of this study is to comprehensively analyze electronic learning in entrepreneurship globally. The research method used is VOSviewer-assisted bibliometric analysis. The review showed that there were 398 academic documents published in the Scopus database between 2001 and 2022. The results showed that the most publications occurred in 2021, and keyword identification formed 7 clusters that grouped research themes in recent years. Based on the studies conducted, this study presents a roadmap for prospective researchers as well as critical themes that are very likely for future research success.